Jews in the Piazza: Jewish Self-government in the Fifteenth-century Kingdom of Naples - Selleri, Vincenzo (European journal of jewish studies, 2017)
This study intends to make a contribution to the literature on Jewish autonomy in the Late Middle Ages by analyzing Jewish political life in the Kingdom of Naples in the fifteenth century. Contrary to Italian and European scholarship which has interpreted Jewry policy in the Kingdom of Naples in the fifteenth century as a direct emanation of the ‘good heart’ of the Aragonese kings, I argue that Jewish charters must be considered the product of Jewish agency. I suggest that the Jewish ruling elites, not the king nor the municipal governmets sought the administrative and juridical separation of the iudece (Jewish Communities) from the municipal governement of southern cities. Considering that Jewish political action, and the administration of the iudeca mirrored that of cities, I argue that Jewish Communities fit perfectly into the Aragonese administrative puzzle.